2012
DOI: 10.1177/105268461202200506
|View full text |Cite
|
Sign up to set email alerts
|

Distributed but Undefined: New Teacher Leader Roles to Change Schools

Abstract: This article examines teacher leader role development and definition by looking at one emergent model of distributed leadership: the hybrid teacher leader (HTL). HTLs are teachers whose official schedule includes both teaching K–12 students and leading teachers in some capacity. Participants included six HTLs across four school districts over 2 years, as well as their administrators. Extensive qualitative data were collected and subsequently analyzed, including interviews, on-site observations, and artifacts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 25 publications
0
63
0
1
Order By: Relevance
“…Killion and Harrison (2006) suggest additional roles such as instructional and curriculum specialist, resource provider, learning facilitator, school leader, and catalyst for change, among others. Some scholars have suggested that it entails even more intensive roles, such as being involved in policy matters (Margolis & Huggins, 2012;Muijs & Harris, 2003) and being partly responsible for change in the whole school organization (Carpenter & Sherretz, 2012;Vernon-Dotson & Floyd, 2012).…”
Section: Defining Teacher Leadershipmentioning
confidence: 99%
“…Killion and Harrison (2006) suggest additional roles such as instructional and curriculum specialist, resource provider, learning facilitator, school leader, and catalyst for change, among others. Some scholars have suggested that it entails even more intensive roles, such as being involved in policy matters (Margolis & Huggins, 2012;Muijs & Harris, 2003) and being partly responsible for change in the whole school organization (Carpenter & Sherretz, 2012;Vernon-Dotson & Floyd, 2012).…”
Section: Defining Teacher Leadershipmentioning
confidence: 99%
“…Identifying and categorizing the teacher leader positions helps to once again validate the leadership already taking place in schools community members other than administrators. Margolis and Huggins' (2012) work underscores the fact that much of the transformation to a distributed model is more importantly a validation and legitimization of leadership that is already happening. Firestone and Distributed Leadership 13 Martinez's (2007) work has focused on how teacher leaders can influence teaching practice and the relationship between teacher leaders and districts in educational change.…”
Section: Background and Needmentioning
confidence: 96%
“…Most importantly, Barth (2001) continues the conversation about what teachers gain by leading: "[Teachers] experience a reduction in isolation; …satisfaction that comes from improving their schools; a sense of instrumentality, investment, and membership in the school community; and new learning about schools, about the process of change, and about themselves" (Barth, 2001, p. 449) Powerful and transformative things can happen when leadership is shared across a school. Margolis and Huggins (2012) and Firestone and Martinez (2007) continued to show how leadership distribution is already happening. Margolis and Huggins (2012) documented "Hybrid teacher leaders" who have formalized schedules that include both teaching students and leading teachers.…”
Section: Background and Needmentioning
confidence: 99%
See 2 more Smart Citations